2018
DOI: 10.1002/cptc.201800144
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy Harvesting with Carbon Nitrides and N‐Heterocyclic Frameworks: Do We Understand the Mechanism?

Abstract: The photocatalytic splitting of water into molecular hydrogen and molecular oxygen with sunlight is the dream reaction for solar energy conversion. For decades, transition metal oxide semiconductors and supramolecular organometallic structures have been extensively explored as photocatalysts for solar water splitting. More recently, polymeric materials consisting of triazine or heptazine building blocks have attracted considerable attention as hydrogen‐evolution photocatalysts. The mechanism of hydrogen evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…The hydrogen bonding is essential for the excited-state PCET reaction which leads to the abstraction of an H-atom from the substrate molecule. 37,41,71 In contrast to optoelectronics, the energy and the properties of the lowest bright 1 ππ* state play a decisive role, in addition to the properties of the S1(ππ*) state. The photon is absorbed by the bright 1 ππ* state which then rapidly (on sub-picosecond time scales) decays to the S1 state by internal conversion.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bonding is essential for the excited-state PCET reaction which leads to the abstraction of an H-atom from the substrate molecule. 37,41,71 In contrast to optoelectronics, the energy and the properties of the lowest bright 1 ππ* state play a decisive role, in addition to the properties of the S1(ππ*) state. The photon is absorbed by the bright 1 ππ* state which then rapidly (on sub-picosecond time scales) decays to the S1 state by internal conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Despite extensive research efforts in the past ten years, the photophysical and photochemical processes underlying the photocatalytic hydrogen evolution reaction with graphitic carbon nitride materials remain a mystery. 7,8 To gain insight into the fundamental photophysics of heptazine-based materials, a heptazine-derived molecular photocatalyst, tri-anisole-heptazine (TAHz), was recently synthesized by Schlenker and coworkers. 9 It was shown that photoexcited TAHz can oxidize water via an H-atom transfer reaction, resulting in the quenching of the excited state of TAHz and the liberation of OH radicals that were detected using terephthalic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, which is conducted as continuation of our investigations on synthesizing new heterocyclic dyes as organic photosensitizers in DSSCs, 35,36 we have aimed at a synthesis of 3 H ‐benzofuro[2,3‐ b ]pyrazolo[4,3‐ f ]quinolines as novel fluorophores as high‐performance organic photosensitizers. The photovoltaic performances of the title compounds are remarkable and comparable to recently heterocyclic dyes as organic photosensitizers 37‐39 . In the process, their physical spectral and analytical data proved to corroborate the structure of the pentacylic heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 59%